Pitfalls in the Diagnosis of Jaundice due to Carcinoma of the Pancreas or Biliary Tree. Issue 5852 (3rd March 1973) - Stern, R. B.; Knill-Jones, R. P.; Williams, Roger
Abstract : Analysis of 56 patients with obstructive jaundice due to carcinoma of the pancreas or extrahepatic biliary tree showed that unexpected features were present in 25%. Presentation with painless jaundice was uncommon, and the symptoms were more often non-specific, with malaise, anorexia, and vomiting. Abdominal pain was frequent, and the condition was found in young patients. One-fifth presented with serum alkaline phosphatase levels of less than 30 K.A. units. Some had high serum aspartate aminotransferase levels, more characteristic of hepatocellular jaundice. A mathematical model may be helpful in correctly weighting these various criteria.